3m=2m+7  

15 Answers | Add Yours

pohnpei397's profile pic

pohnpei397 | College Teacher | (Level 3) Distinguished Educator

Posted on

As far as algebra problems go, this one is pretty straightforward.

Remember that whenever you are trying to solve for a variable, you want to get all the terms with a variable on one side of your equation and all the terms without on the other.   In this equation, you only have one term without a variable.  That means all you have to do is get the variables on the other side of the equation.  In this case, you can do that by subtracting 2m from both sides.  That gets you

3m - 2m = 7

or

m = 7

fashionableb1's profile pic

fashionableb1 | Student, Grade 10 | (Level 1) Salutatorian

Posted on

3m = 2m + 7

3m - 2m = 7

m = 7

udonbutterfly's profile pic

udonbutterfly | Student, College Freshman | (Level 1) Valedictorian

Posted on

3m = 2m + 7 This equation is pretty simple and only takes one step to get the answer.

In order to solve for m you are going to subtract 2m on both sides

3m - 2m = 2m + 7 - 2m  The 2m on the right side of the equation will be cancelled out.

m = 7 Here is your answer!

jess1999's profile pic

jess1999 | Student, Grade 9 | (Level 1) Valedictorian

Posted on

3m = 2m + 7

To solve this equation, first subtract 2m from both sides this way " m " would be on the same side which makes the equation easier to solve.

By subtracting 2m from both sides your equation should be :

m = 7 which is also your answer

zumba96's profile pic

zumba96 | Student, Grade 11 | (Level 3) Valedictorian

Posted on

3m=2m+7 

This is fairly simple compared to other problems you will encounter

Move like terms to one side

3m-2m=7, the numbers cancel so it becomes m=7

atyourservice's profile pic

atyourservice | Student, Grade 11 | (Level 3) Valedictorian

Posted on

3m=2m+7

move the like terms on the same side so minus 2m

3m - 2m = 7

combine like terms

m = 7

Wiggin42's profile pic

Wiggin42 | Student, Undergraduate | (Level 2) Valedictorian

Posted on

3m = 2m + 7

You can solve this in a single step. Simply bring the 2m to the other side

3m - 2m = 7

-> m = 7

princessenotes's profile pic

princessenotes | Student, Undergraduate | (Level 1) Honors

Posted on

You should have learned this in Middle School.

YOu move 2m to the other side of the equal sign.

m = 7

That is the answer.

 

Also, if you need anymore help, you can email my friend who is a professor at helpmathtutor@gmail.com

 

krishna-agrawala's profile pic

krishna-agrawala | College Teacher | (Level 3) Valedictorian

Posted on

The method of solving an equation with a single variable - for example, "m" in the given question is as follows.

Shift all the terms containing the variable on one side of the equation, say left hand side, and all other terms- which are only plain numbers - to other side. The rules for shifting a term from one side to the other is that the term remain same except that the sign of the term is reversed, that is, minus becomes plus and plus becomes minus. Once this is done all the terms on each side are added and subtracted together as per their signs. This will result in equation of the form:

ax = b

where x is the variable (in the given question it is designated as m), and a and b are numbers.

Then value of the variable x is given as x = b/a.

To solve the given question we will first transfer the term 2m on the right hand side to the left hand side. In this process the term will become from positive to negative. Thus the given equation becomes:

3m - 2m = 7

Subtracting 2m from 3m on the left hand side, the equation then becomes:

m = 7

This gives us the require answer: m is equal to 7.

neela's profile pic

neela | High School Teacher | (Level 3) Valedictorian

Posted on

3m=2m+7.

To solve for m, which is unknown.

Solution: We use simple similar operations( like adding, subtracting multiplication or division)  keeping the equality on both sides.

Subtract 2m both sides of the given equation . This action retains balnce and m vanishes on right and m remains only on left:

3m-2m = 2m+7-2m , resulting in

m = 2m-2m+7 or

m = 0+7 or

m = 7

We’ve answered 318,915 questions. We can answer yours, too.

Ask a question